Targeting the cGAS-STING pathway: emerging strategies and challenges for the treatment of inflammatory skin diseases - Haoyun Luo; Tian Tian; Chenmin Hu; Fei Hao (Frontiers in Pharmacology)
The cGAS-STING signaling pathway is a major component of innate immunity. It is critical for identifying cytoplasmic DNA, triggering immune responses, and is linked to several diseases and malignancies. The inflammatory infiltrates and elevated cytokine expression characteristic of dermatological inflammatory disorders have drawn attention to the potential role of the cGAS-STING pathway, positioning it as an emerging focus of scientific investigation. Therapeutic strategies targeting the cGAS-STING signaling axis have been explored for the treatment of inflammatory dermatoses, with several inhibitor classes under investigation, such as cGAS inhibitors, STING palmitoylation blockers, STING trafficking suppressors, and nanoformulated inhibitors. Nevertheless, there are problems in both this pathway and drug research still left to be solved: inhibitors are not generally specific enough, drugs are not generally bioavailable enough, and there is an imbalance between the two—immunosuppression and the immune response. The several possible approaches in the future directions include combination therapy, multi-omics integration, and precision medicine approaches to treat these diseases. Given its broad immunomodulatory effects, there is high potential for clinical application of the cGAS-STING pathway modulators.